Development of E-Worksheets for Students with Special Intelligence and Special Talents in English Reading Learning in Elementary Schools - Sri Hartati; Syarfuni Syarfuni; Siti Mayang Sari (FKIP - Universitas Riau, 2026)
The main objective of English learning is to build motivation, self-confidence, and basic communicative competence in English in elementary schools. However, researchers found that there is no language learning media for exceptionally gifted and intelligent children (CIBI) based on a digital platform. The purpose of this study is to develop a flipbook-based e-worksheet design using Google Classroom. A Research and Development (R&D) approach was applied in this study. A Likert-scale assessment questionnaire was used to collect data on the suitability of the media, and the Class test instrument was used to test its effectiveness. The research findings, the average score of the media validity test was 92% with respectable credibility, while the average score of the material validity was 95% with excellent quality. The average knowledge score for the large-scale test was 95, while the average knowledge score for the small-scale effectiveness test was 93. There was a 27 percent increase in learning outcomes. This study provides valuable empirical insights into the effectiveness of using e-worksheets in improving English language skills and encouraging CIBI students' engagement, while also providing actionable recommendations for educators aiming to integrate advanced technology into language teaching.